2021
DOI: 10.1002/anie.202104035
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Synthesis Based on Reactions of Ionic Liquids and Deep Eutectic Solvents

Abstract: Michael Ruck received his PhD from the University of Stuttgart in 1991 with Prof. Arndt Simon. After his habilitation at the University of Karlsruhe in 1997, he was aHeisenberg fellow of the German Science Foundation. Since 2000 he has been Full Professor of InorganicC hemistry at the Technische UniversitätD resden, where he has served as Dean of the Faculty of Science and Vice Rector.Hehas repeatedly been appointed aF ellow of the Max Planck Society and awarded the Steinhofer Research Award and the Will Klebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(85 citation statements)
references
References 210 publications
(553 reference statements)
0
73
0
Order By: Relevance
“…elements, oxides, sulfides) at moderate temperatures, in some cases even at room temperature, without the need for special reaction vessels (autoclave, high-temperature or high-pressure equipment) in normal flasks, making them accessible for downstream chemistry. 1,2 The IL may be a stable and inert solvent or it acts as a reactant that is altered by chemical reaction with the substances to be dissolved. 1–14 Sometimes ions or molecules of the IL are incorporated into the solid products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…elements, oxides, sulfides) at moderate temperatures, in some cases even at room temperature, without the need for special reaction vessels (autoclave, high-temperature or high-pressure equipment) in normal flasks, making them accessible for downstream chemistry. 1,2 The IL may be a stable and inert solvent or it acts as a reactant that is altered by chemical reaction with the substances to be dissolved. 1–14 Sometimes ions or molecules of the IL are incorporated into the solid products.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The IL may be a stable and inert solvent or it acts as a reactant that is altered by chemical reaction with the substances to be dissolved. 1–14 Sometimes ions or molecules of the IL are incorporated into the solid products. As a generally less expensive alternative to ILs, deep eutectic solvents (DES) have also been tested for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DESs have attracted the attention of the scientific community because of their potential applications. These mixtures can be used in organic synthesis, electrochemistry, extraction media [30][31][32][33][34], biotechnology or biodiesel [35][36][37] synthesis and separation processes [38,39], as a solvent in biological assays or enzymatic reactions [40], in biocatalysis [41,42], or in biomedical applications [43][44][45][46]. Additionally, they have been used in the pharmaceutical industry as excipients for increasing the solubility of hydrophobic drugs, or in drug delivery formulations [47][48][49][50][51].…”
Section: Deep Eutectic Solvents (Dess)mentioning
confidence: 99%
“…Due to the nature and versatility of DESs, these mixtures are attracting attention from the academic and industry sectors. It has been demonstrated that DESs can be used for many applications such as synthesis [18][19][20], separation processes [21,22], extraction [23][24][25][26][27][28], biocatalysis [29], nanomaterials, biotechnology [12,13], electrochemistry [30,31], food [32], cosmetics, pharmaceuticals [33][34][35][36][37][38], or as a biofuel [12,14,16,25,39]. DESs are also useful in the pharmaceutical industry as excipients for the delivery of hydrophobic drugs or as a vehicle [40].…”
Section: Introductionmentioning
confidence: 99%